2017
DOI: 10.1093/ejcts/ezx025
|View full text |Cite
|
Sign up to set email alerts
|

Common atrioventricular valve failure during single ventricle palliation†

Abstract: Patients with single ventricle physiology and common atrioventricular valve experience a continuous decline in valve function. The majority of patients experience valve failure in the first 30 years of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…In a study by Buratto and colleagues 17 of unbalanced atrioventricular septal defects undergoing single-ventricle palliation, 32% needed valve repair and had an early mortality of 18%, and 32% needed further valve intervention. King and colleagues 18 reported on 114 patients with Fontan circulation with common atrioventricular valves and found that 28 patients required valve intervention, and 24 of those patients underwent repair at the first intervention. Of the patients who underwent repair, 67% experienced valve repair failure that was defined as the need for reintervention for moderate or more regurgitation.…”
Section: What's Badmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Buratto and colleagues 17 of unbalanced atrioventricular septal defects undergoing single-ventricle palliation, 32% needed valve repair and had an early mortality of 18%, and 32% needed further valve intervention. King and colleagues 18 reported on 114 patients with Fontan circulation with common atrioventricular valves and found that 28 patients required valve intervention, and 24 of those patients underwent repair at the first intervention. Of the patients who underwent repair, 67% experienced valve repair failure that was defined as the need for reintervention for moderate or more regurgitation.…”
Section: What's Badmentioning
confidence: 99%
“…Of the patients who underwent repair, 67% experienced valve repair failure that was defined as the need for reintervention for moderate or more regurgitation. 18 The 4-year freedom from repair failure was a disappointing 50%. 18 Similarly in the study of King and colleagues, 1 common atrioventricular valve was a factor for valve repair failure on univariate analysis, with 68% failing as compared with 14% of mitral valve repairs.…”
Section: What's Badmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderate-to-severe AVV regurgitation is an independent predictor of mortality and reoperation after single-ventricle palliation. 3 Patients with single-ventricle physiology and common AVV are at risk of progressive AVV insufficiency after Fontan operation, 2 as occurred in the patient described herein. We have previously demonstrated that AVV repair is especially difficult in unbalanced AVSD 3 and dextrocardia 4 using conventional techniques.…”
Section: Discussionmentioning
confidence: 79%
“…1 Common atrioventricular valves (AVV) often become insufficient in patients with univentricular physiology, leading to heart failure. 1,2 We have recently observed that outcomes of children with AVSD who reach Fontan circulation are not as bad as previously thought, provided that the AVV remains competent. 1 Common AVV surgery is associated with substantial mortality and reoperation rates.…”
mentioning
confidence: 90%